Analysis of the physical development and somatotype of girls and females involved into dancing and gymnastic sports - Podrigalo, L. V.; Artemieva, H. P.; Rovnaya, O. A.; Panshyna, A. D.; Ruban, L. A.; Merkulova, T. V.; Galashko, M. M.; Chernukha, O. V. (Physical Education of Students, 2019)
Purpose: The comparative analysis of the physical development and somatotype of girls and females involved in dancing and gymnastic sports (acrobatic rock and roll, sports aerobics). Material: The study involved 45 girls and females. Group 1 - acrobatic rock and roll (n = 25, age - 13.00 ± 0.41 years); Group 2 - sports aerobics (n = 20, age - 19.70 ± 0.59 years). It was determined the length and body weight. It was evaluated the level and harmony of physical development. The bioimpedance method was applied to determine the composition of muscle and fat tissue, the level of visceral fat. It was evaluated the body mass index, water composition in the body. The results are evaluated by applying parametric and non-parametric statistical indicators. Results: The average level of physical development dominates in athletes. Its specific gravity is: group 1 - (64.00 ± 9.60)%; group 2 - (50 ± 11.18)%. Rather high prevalence of the level below the average: group 1 - (20.00 ± 8.00)%; group 2 - (25.00 ± 9.68)%. The proportion of athletes with harmonious development was: group 1 - (64.00 ± 9.60)%; group 2 - (50.00 ± 11.18)%. The disharmony of physical development due to overweight: group 1 - (20.00 ± 8.00)%; group 2 - (30.00 ± 10.25)%. The disharmony of development due to underweight: group 1 - (16.00 ± 7.33)%; group 2 - (20.00 ± 8.94)%. The average values of fat tissue reflect its normal composition in both groups. In group 1, was determined the normal for the age fat composition in (52.00 ± 9.99)%; low level of fat had (48.00 ± 9.99)%. In group 2, the normal fat composition was found in (75.00 ± 9.68)%. The increased fat composition was (15.00 ± 7.98)% of female athletes. The reduced fat composition was (10.00 ± 7.61)% of female athletes. The level of visceral fat in athletes of group 2 was within the age norm. Female athletes of group 1 were characterized by virtually no visceral fat. The specific gravity of muscle tissue in all athletes was above the average for this age group. Group water composition in both groups was average. Conclusions: Most athletes have an average harmonious physical development. Deviations of physical development are most often associated with underweight. It is determined the increase in the composition of muscle mass above the average age standards for all female athletes. The composition of fat tissue in 52% of female athletes of the younger group corresponded to the average value. The rest of the athletes had a fat composition below normal. In the older group: 75% of athletes had an average fat composition; 15% of athletes had a reduced fat composition; 10% of athletes had a high fat composition. It was determined the significant differences between groups. The female athletes of group 1 had smaller values of body length, body weight, the specific gravity of fat tissue and visceral fat, body water composition, and body mass index. Females of group 1 had a big specific gravity of muscle tissue. The application of the bioimpedance method has significantly expanded the data obtained in the analysis of anthropometric indicators and indices. This method can be recommended for monitoring the functional condition of athletes dancing and gymnastic sports.